PENGGUNAAN MEDIA PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS TENTANG PERJUANGAN PROKLAMASI KEMERDEKAAN INDONESIA - Ira Meiyana, - (2020)
ABSTRACT USE OF PUZZLE MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES IN LEARNING SOCIAL SCIENCE CONCERNING THE STRUGGLE OF INDONESIA'S INDEPENDENCE PROCLAMATION Ira Meiyana Elementary School Teacher Education Program, Serang Regional Campus, Indonesia University of Education This research is based on observations, that there are still many students who are less enthusiastic and enthusiastic in participating in learning social science. The purpose of this research is to know the steps in using puzzle media and to know the increase in student learning outcomes through the use of puzzle media in learning social science about the struggle for the proclamation of Indonesian independence. The approach used in this study is a qualitative approach, for research methods using classroom action research methods. The data collection techniques used are observation, test, and documentation. Data analysis was performed by researchers to determine the results of the data collection techniques applied. Data analysis was performed using 3 activities namely data reduction, data presentation, and data verification. In this class action research using cycle I and cycle II which includes action planning, action implementation, action observation and action reflection. The results of the study found in the first cycle that students who scored above 70 were 5 people (50%) and students who scored below 70 were 5 people (50%). Then in the second cycle all students scored above 70. Based on the first and second cycle students experienced an increase of 50%. Therefore the researcher concludes that puzzle media can improve student learning outcomes in Social Sciences subjects in Class V SDN Cibarani II. Keywords: Puzzle media, learning outcomes